AB1108 Handling of de novo arthritis in adults by general practitioners: a survey in a french cohort. (15th June 2017) - Lecauchois, S; Gentile, S; Champsaur, P; Mattei, J-P; Dillinger, L; Goeb, V; Guis, S
Abstract : Background: A guide of good clinical practice regarding de novo arthritis in adults has been edited. Objectives: The aim of this work is to identify whether the diagnostic and therapeutic tools proposed by general practitioners (GPs) to adults with a de novo arthritis is in line with the corresponding recommendations. Methods: A questionnaire regarding the characteristics and the handling of de novo arthritis in adults has been submitted to 300 GPs chosen randomly from a French cohort database. The study period was from February 2015 to February 2016. Fifty seven GPs participated in the study (19%). Results: No particular specificity was identified in the GP group. The age of patients ranged between 40 and 75 yo. The prevalence of arthritis was less than 5% among the GPs patients. The relative number of each category of arthritis was rheumatoid arthritis (29%), spondyloarthritis (14%), PPR (8%), other kinds of microcrystalline arthritis: chondrocalcinosis, (38.4%), gout (11, 6%). Joints with mechanic degenerative effusion related to osteo-arthritis might be misdiagnosed as an inflammatory arthritis. The knee was the most frequently involved joint in arthritis. The initial paraclinical survey was related to biology. Most of the patients were treated with NSAI as an initial intent. A corticoids-based therapy was proposed to 1.4% of the patients and the corresponding specialist was a rheumatologist (98%). Conclusions: The de novo arthritis prevalence for GPs is less than 5% with the knee being the most affected joint. Most frequently, GP are faced with gout, rheumatoid arthritis and spondyloarthritis. The handling is in line with the corresponding guide of good clinical practice. Disclosure of Interest: None declared